2017
DOI: 10.1093/migration/mnx066
|View full text |Cite
|
Sign up to set email alerts
|

Resituating relaunched migration systems as emergent entitiesmanifested ingeographic structures

Abstract: While important and timely, the recent effort to 'relaunch' migration systems as emergent entities is premised on a mischaracterization and subsequent dismissal of decades of research showing that systems are ultimately expressed in geographic structures in the form of migration networks comprised of a set of places that are connected to one another by migration flows. In this paper, we reconcile this relaunch with past research on migration systems by considering whether and how changes in some of the actors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Feedback in this context is then relative to an individual's earlier migration decisions and can be linked to migration histories and life course decisions on which there is a vast literature (Skeldon, 1995;Odland and Shumway, 1993;DaVanzo, 1982 and1983;Carling, 2012). We aim to prove that this approach can provide interesting insights as well as be applied empirically and hope to contribute to the renewed interest in migration systems as discussed in Bakewell (2014) and DeWaard and Ha (2019).…”
Section: The Conceptual Frameworkmentioning
confidence: 97%
“…Feedback in this context is then relative to an individual's earlier migration decisions and can be linked to migration histories and life course decisions on which there is a vast literature (Skeldon, 1995;Odland and Shumway, 1993;DaVanzo, 1982 and1983;Carling, 2012). We aim to prove that this approach can provide interesting insights as well as be applied empirically and hope to contribute to the renewed interest in migration systems as discussed in Bakewell (2014) and DeWaard and Ha (2019).…”
Section: The Conceptual Frameworkmentioning
confidence: 97%
“…and ideas, and systems perspectives focus analytically on the factors that stimulate, direct, and sustain these origin-destination flows (Massey et al 1998). While systems perspectives are as “old as the scientific study of migration” (Fawcett 1989, 671), data improvements in the 1980s increased scholarly interest in this approach, and substantial theoretical and empirical progress has been made since then (DeWaard and Ha 2019; Hauer, Holloway and Takashi 2020b).…”
Section: Migration Systems As An Analytical Lensmentioning
confidence: 99%
“…Previous research using a migration systems approach (Bakewell 2014; DeWaard and Ha 2017; Mabogunje 1970) has explored migration responses to Hurricanes Katrina and Rita (Curtis, Fussell, and DeWaard 2015; DeWaard, Curtis, and Fussell 2016; Fussell, Curtis, and DeWaard 2014). These studies have shown that migration systems from and to hurricane‐affected coastal counties in the Gulf of Mexico intensified, and involved more spatially concentrated and urban counties in the years immediately following the active and costly 2005 hurricane season (Curtis et al 2015).…”
Section: Migration In Response To Environmental Eventsmentioning
confidence: 99%